SECOND GRADE MHD FLOW AND HEAT TRANSFER OVER A STRETCHING SHEET WITH VISCOUS AND OHMIC DISSIPATIONS - Sanjayanand, Emmanuel (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Two dimensional second grade fluid has been considered for analysis. Basic governing equation of velocity and temperature are partial differential equation which is converted to ordinary differential equation by using transformation variable. Employing fifth order Runge-Kutta-Fehlberg method with shooting to solve momentum equation. The results are analysed for the situation when stretching boundary sheet is prescribed by non-isothermal temperature and variable heat flux, varying quadratically with the flow directional coordinate x..